A robust 2D organic polysulfane nanosheet with grafted polycyclic sulfur for highly reversible and durable lithium-organosulfur batteries. (March 2019) - Hu, Hao; Zhao, Bote; Cheng, Haoyan; Dai, Shuge; Kane, Nicholas; Yu, Ying; Liu, Meilin
Abstract: Organic polysulfanes are new type of attractive organosulfur electrode materials for next generation lithium-sulfur (Li-S) batteries because of their high sulfur content, low cost, and desirable energy density. However, conventional organic polysulfanes usually suffer from poor reversibility due to structure variation and irreversible conversion during cycling. Here we report the synthesis and characterization of a novel two-dimensional (2D) organic polysulfane with a unique molecular structure of polycyclic sulfur directly substituting the carboxyls of poly(acrylic acid) and grafted on the carbon chain through a coupling reaction with KI as a catalyst and KCl as a template. The obtained organic polysulfane nanosheets with 72 wt% sulfur (OPNS-72) exhibit high initial capacity of 891 mAh/g (based on whole composite), excellent cycling stability (0.014% capacity fading per cycle over 620 cycles at 1 C rate), superior rate capability (562 mAh/g at 10 C) and high mass loading of 9.7 mg/cm 2 . The remarkable cycling stability of the Li-S battery is attributed to the structural stability and highly reversible electrochemical reaction of the OPNS-72 electrode, as confirmed by the TEM image after cycling and operando Raman spectroscopy measurements under battery operating conditions. Further, the developed synthesis approach is applicable for the preparation of other organic polysulfane nanosheets as highly reversible electrodes for Li-S batteries. Graphical abstract: A novel two-dimensional organic polysulfane with polycyclic sulfur directly grafted on the carbon chain of poly(acrylic acid) is prepared through a coupling reaction with KI as a catalyst and KCl as a template. Benefiting from the stable carbon chains, the organic polysulfane nanosheets exhibit high specific capacity, excellent cycling stability and superior rate capability. fx1 Highlights: A two-dimensional, ultra-thin, organic polysulfane with controllable sulfur content (0 to 93%) can be synthesized through a coupling reaction with KI as a catalyst and KCl as a template. The sulfur cluster was grafted on the carbon frame in the organic polysulfane. This structure can effectively buffer the volume variation during cycling. The ultrathin organic polysulfane nanosheet morphology facilitates fast diffusion of lithium ions and electrons, leading to enhanced rate capability and power density. The unique organosulfur-based electrode architecture and high sulfur content result in high capacity and good capacity retention. The organosulfur-based electrode of OPNS-72 still reveals a good cycling performance with a remarkably high mass loading of 9.7 mg/cm 2 .